2010
DOI: 10.1080/08941920802684146
|View full text |Cite
|
Sign up to set email alerts
|

Factors Impacting Agricultural Landowners' Willingness to Enter into Conservation Easements: A Case Study

Abstract: Agricultural lands offer an abundance of environmental goods and services, yet face residential development pressures. Conservation easements are frequently used to protect both productive land and environmental amenities. The landowner retains ownership, and may donate development rights or receive compensation for permanently limiting development on the property. Focus groups were conducted with agricultural landowners in Wyoming and Colorado to explore factors affecting their preferences for conservation ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
3
29
0
Order By: Relevance
“…Inflexibility on the part of government agency easement holders may also be suppressing or preventing management actions on some easement properties, as evidenced by the decreased wildlife management reported on federally held easements (Rissman et al 2013). However, easement-holding organizations could encourage enhanced management by incorporating mechanisms in the easement instrument that allow for more adaptive management strategies (Miller et al 2010;Rissman 2010;Rissman et al 2013). Several landowners expressed frustration concerning the lack of adaptive management accommodation within the framework of their easement restrictions.…”
Section: Discussionmentioning
confidence: 96%
“…Inflexibility on the part of government agency easement holders may also be suppressing or preventing management actions on some easement properties, as evidenced by the decreased wildlife management reported on federally held easements (Rissman et al 2013). However, easement-holding organizations could encourage enhanced management by incorporating mechanisms in the easement instrument that allow for more adaptive management strategies (Miller et al 2010;Rissman 2010;Rissman et al 2013). Several landowners expressed frustration concerning the lack of adaptive management accommodation within the framework of their easement restrictions.…”
Section: Discussionmentioning
confidence: 96%
“…Holding an ethic of stewardship has been found to motivate landowners to engage in land protection programs (Lynch and Lovell, 2003;Miller et al, 2011;Natori and Chenoweth, 2008;Rissman et al, 2007). The role of place attachment, however, is less consistently related to conservation behaviors.…”
Section: Motivations For Conservation Easementsmentioning
confidence: 96%
“…Miller et al (2011) posited that landowners’ decisions to adopt an easement are motivated by the desire to conserve the habitat of wild animals, open space, agricultural production, and the cultural and economic resources of their community. Miller et al's (2011) conclusions are consistent with those of Kline and Wichelns’ (1994), who found that landowners’ depth of understanding of land conservation issues affects the conservation measures they adopt on their property.…”
Section: Introductionmentioning
confidence: 99%
“…Miller et al (2011) posited that landowners’ decisions to adopt an easement are motivated by the desire to conserve the habitat of wild animals, open space, agricultural production, and the cultural and economic resources of their community. Miller et al's (2011) conclusions are consistent with those of Kline and Wichelns’ (1994), who found that landowners’ depth of understanding of land conservation issues affects the conservation measures they adopt on their property. Other motivations for conservation action on private property are altruism (McLeod et al 1999), emotional connection to the land (de Haven‐Smith 1988; Robinson 2004), environmental values (Jacobson 2002; Ryan et al 2003; Miller et al 2011), and protection of open space for social reasons (Miller et al 2011).…”
Section: Introductionmentioning
confidence: 99%